Gdańsk. Zniszczenia i odbudowa Kościół N. P. Maryi, ulica Mariacka i Świętego Ducha. Cz. 1 / Kaziemierz Lelewicz. - Lelewicz, Kazimierz (1896-1986) (1945)
Przedstawia zdjęcia z odbudowy Gdańska w l. 1945-1970.